2018
DOI: 10.3390/sports6020055
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reflection to Improve Goal-Directed Self-Talk on Endurance Performance

Abstract: We investigated the effects of an intervention that encouraged reflection on organic self-talk used during endurance performance. Using an experimental design, we compared the effects of enhancing metacognitive skills by (a) planning and (b) reviewing and evaluating goal-directed self-talk. Participants completed three time-to-exhaustion cycling task trials in which we hypothesized that the intervention group would perform significantly better than the control group. Further, we expected a reduction in perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…Nevertheless, the available studies already shed a nuanced light on mechanisms and moderators of if-then planning in sports. If-then planning modulates perceptions of exertion and experienced pain in endurance tasks (Bieleke & Wolff, 2017;Latinjak et al, 2018;Wolff et al, 2018). Moreover, it attenuates the arousal that accompanies performance in challenging situations (Stern et al, 2013;Wilczynska et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the available studies already shed a nuanced light on mechanisms and moderators of if-then planning in sports. If-then planning modulates perceptions of exertion and experienced pain in endurance tasks (Bieleke & Wolff, 2017;Latinjak et al, 2018;Wolff et al, 2018). Moreover, it attenuates the arousal that accompanies performance in challenging situations (Stern et al, 2013;Wilczynska et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these studies focused on static muscular endurance performance, predominantly via weight-holding tasks (Bieleke & Wolff, 2017;Hirsch et al, 2020;Thürmer et al, 2017;Wolff et al, 2018) and once in a posture-holding yoga task (Wang et al, 2019). Only one study used a cycling task to examine whole-body endurance performance (Latinjak et al, 2018). Common to all studies is their reliance on university student samples as well as on laboratory experiments with highly standardized tasks that maximize internal validity at the expense of external validity.…”
Section: Endurance Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Compared to a control group, participants who had formed if-then plans performed better in both studies. However, studies that investigated the effects of an if-then planning intervention on static muscular endurance (e.g., individual weight-holding task; Bieleke & Wolff, 2017;Hirsch et al, 2020;Wolff et al, 2018) or whole-body endurance (Latinjak et al, 2018) observed no performance improvements. Interestingly, if-then planning still affected important correlates of endurance performance like the perception of effort (Bieleke & Wolff, 2017) and the activation of prefrontal cortex areas (Wolff et al, 2018).…”
Section: Optimizing Performance With Tailored Self-regulatory Intervementioning
confidence: 99%
“…Compared with the existing self-talk literature that deals intensively with research on interventions using predetermined cue words (Tod et al, 2011), the research with reflexive self-talk interventions (aka., goal-directed self-talk interventions) is still in its infancy (Latinjak et al, 2016, 2018). Nonetheless, diverse psychotherapeutic approaches [e.g., Rational Emotive Therapy (Ellis, 1976) and Cognitive-Behavior Modification (Meichenbaum, 1977)] previously applied effectively to the sports setting (Neil et al, 2013; Turner and Barker, 2014) serve as indirect support for the efficacy of reflexive self-talk interventions in sport.…”
Section: Introductionmentioning
confidence: 99%